PELAKSANAAN PROMOSI DESA WISATA KOTO SENTAJO OLEH PEMERINTAH KABUPATEN KUANTAN SINGINGI - Resma Astuti Angesti Rahayu; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine how the promotion of Rural Tourism Koto Sentajo conducted by Singingi Kuantan District Government as well as to determine the response of tourists to the promotion of tourism village of Koto Sentajo conducted by the District Government Singingi Such Kuantan.In this study the research methods that I use is a quantitative method with a descriptive approach, where researchers tried to describe to explain in detail the issues to be examined based on data that was obtained from a questionnaire research reports / questionnaires have been collected, then analyzed and spoken in the form sentence to then be deduced. Processing results are then presented in the form of numbers -angka so that gives an impression more easily captured its meaning by anyone who needs information about the existence of these symptoms. While data collection techniques in this study using observation, interviews, documentation and questionnaires / questionnaire.Based on the research that has been done, the promotion of village tourism in some media have not fully achieve maximum results, but the overall promotion of tourism village conducted by Regency Kuantan Singingi already considered good.Keywords : Tourism Marketing Promotion, Tourism Village, Village Tourism Koto Sentajo